X-ray diffraction for the determination of residual stress of crystalline material: an overview - Lodh, Arijit; Thool, Khushahal; Samajdar, Indradev (Springer, 2022)
Though there are a variety of experimental techniques available for residual stress measurements, diffraction-based measurements have the unique advantage of estimating the individual components of the residual strain matrix in a crystalline material. This is then converted to residual stresses with appropriate continuum elasticity model(s) and X-ray elastic constants. In particular, measurements based on electron or neutron diffractions have their complexities or availability issues. The laboratory X-ray diffraction, on the other hand, may provide an easy resource and an effective tool. Such measurements range from two tilt methods to more extended d-sin2ψ measurements and multiple {hkil} grazing incident X-ray diffraction. Measurements can even be conducted on single crystals with micro-Laue diffraction and extended to stress ODF (orientation distribution function) calculations. These techniques are unquestionably extremely specialized, where measurement uncertainty plays an important role in the effectiveness plus reproducibility of the data. Unfortunately, standard textbooks or review articles typically describe some, but not all, of the techniques. In this overview, different techniques of X-ray diffraction for the determination of residual stresses in crystalline material have been summarized. It is hoped that potential users may benefit from the deliberations.
Keywords: Residual stress; X-ray diffraction; Grazing incident X-ray diffraction; Micro-Laue diffraction; Stress ODF